Peningkatan Kemampuan Menceritakan Pengalaman Melalui Metode DRILL Kelas III SDN 012 Kabun Kabupaten Rokan Hulu - Untung Sugianto (JURNAL PENDIDIKAN ROKANIA, 2018)
Classroom Action Research was conducted in class III Elementary School 012 Kabun Rokan Hulu. Classroom Action Research was started on 17 to 29 October 2016. Methods of data collection used in this study is non-test and test. The results of teacher observation showed a good improvement and change from cycle I of meeting I up to II cycle of meeting II, that is from 78, 84, 90 up to 96. Learning outcomes show a good improvement and change from cycle I of meeting I up to II meeting cycle II, from 71, 78, 85 to reach 94